The Role of Artificial Intelligence in the Development of Digital Era Educational Progress - Baso Intang Sappaile; Arnes Yuli Vandika; Much Deiniatur; Nuridayanti Nuridayanti; Opan Arifudin (Journal of Artificial Intelligence and Development, 2024)
In recent years, the transformative impact of artificial intelligence (AI) on educational progress in the digital era has been revealed. This research aims to explain how AI can revolutionize the educational landscape, driving inclusivity, equality, and innovation. This research method uses a qualitative approach and a multilateral approach which includes theoretical analysis and empirical findings. This research explains the role of AI in personalized learning, accessibility, educator empowerment, and ethical considerations. These findings reveal the potential for AI to enhance the learning experience by providing customized content, encouraging inclusivity through flexible learning modalities, and empowering educators with actionable insights. However, ethical issues such as data privacy and algorithmic bias require careful consideration. The study concludes with recommendations for future research, advocating further exploration of the efficacy of AI in addressing specific educational challenges and interdisciplinary collaboration to inform the responsible integration of AI in education, ultimately paving the way for a more equitable and innovative educational landscape in the digital world. era.